Non-fluoroscopic catheter ablation: A randomized trial - Pires, Leonardo Martins (Indian Pacing Electrophysiol J, 2019)
BACKGROUND: Catheter ablation provides curative treatment for tachyarrhythmias. Fluoroscopy, the method used for this, presents several risks. The electroanatomical mapping (MEA) presents a three-dimensional image without using X-rays, and may be adjunct to fluoroscopy. OBJECTIVES: We evaluated the possibility of performing catheter ablation with the exclusive use of electroanatomical mapping (MEA), dispensing with fluoroscopy. We compared the total time of procedure and success rates against the technique using fluoroscopy (RX) with emission of X-rays. METHODS: Randomized, unicentric, uni-blind study of patients referred for tachyarrhythmia ablation. RESULTS: Twelve patients were randomized to the XR group and 11 to the EAM group. The mean age was 48.5 (±12.6) vs 46.3 (±16.6) (P = ns). Success occurred in 11 patients (91.7%) in the RX group and 9 (81.8%) in the MEA group (P = 0.46). The procedure time in minutes was higher in the MEA group than in the RX group (79-47-125min vs 49-30-100min; P = 0.006). The mean fluoroscopy time was 11 ± 9 min versus zero (RX vs MEA: P < 0.001). The mean radiofrequency applications were lower in the RX group against the MEA group (6 ± 3.5 × 13.2 ± 18.2 p < 0.019). There were no complications. CONCLUSION: MEA opened new therapeutic possibilities for patients with arrhythmias, reducing the risk of radiation. In this study, it was possible to demonstrate that it is feasible to perform ablation only with the use of MEA, with similar success with fluoroscopy, at the expense of a longer procedure time.